Rocky shore macroalgae communities of the Azores (Portugal) and the British Isles: a comparison for the development of ecological quality assessment tools - Wallenstein, Francisco (2013)
IV Congresso da Ordem dos Biólogos e II Congresso dos Biólogos dos Açores (Painel Biologia Marinha e Oceanografia). Ponta Delgada, Açores, 13-15 de Outubro de 2011.